Using Spiral Dynamic Theory for Adult Civic Engagement Research and Social Justice Education - Lisa R. Brown (Adult Education Research Conference, 2016)
Empirical civic engagement research based in a South American context. Participants included adult learner populations engaged in revolutionary protests that opposed private for-profit education in Chile. Findings were higher order Spiral Dynamic Theory thinking at the for-profits and lower civic engagement.
Keywords: Civic Engagement; Educationness; International Adult Education; Memetics; Spiral Dynamic Theory